2004
DOI: 10.1038/sj.pcan.4500749
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of apoptotic and cell cycle regulatory proteins in distinct histopathologic components of benign prostatic hyperplasia

Abstract: Introduction: Benign prostatic hyperplasia (BPH) is a slowly progressive abnormal glandular enlargement with heterogeneous morphology. Disruption of apoptotic pathways has been suggested as an important regulatory mechanism in this common and significantly morbid disease. Methods: Prostatic tissue from 20 patients with BPH and no prior or subsequent prostatic carcinoma was obtained by transurethral prostatectomy (TURP) at the University of California Davis. Apoptotic regulatory proteins: BCL2, BAX and p27 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…This ensures maximal objectivity in the assessment of the results. In accordance with other studies, it has been shown that p27 (Kip1) is significantly up-regulated in BPH as compared with PCa and HTPCa [14,15]. The difference was higher in all tissue structures except the prostatic stroma.…”
Section: Discussionsupporting
confidence: 90%
“…This ensures maximal objectivity in the assessment of the results. In accordance with other studies, it has been shown that p27 (Kip1) is significantly up-regulated in BPH as compared with PCa and HTPCa [14,15]. The difference was higher in all tissue structures except the prostatic stroma.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore decrease in the expression of these genes could negatively regulate cell cycle progression (Fig. 4), cell proliferation, angiogenesis, motility, metastasis, and cell signaling [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-apoptotic Bcl-2 over-expression has been reported in several human cancers, including prostate cancer, diffuse large B-cell lymphoma (DLBCL), melanoma, etc. [ 56 58 ], resulting in protection of cancer cells from apoptosis or inhibition of TRAIL-induced apoptosis [ 59 , 60 ]. Overexpression of Bcl-xL has also been reported in colorectal cancer and Kaposi's sarcoma [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%